1985
DOI: 10.1139/v85-111
|View full text |Cite
|
Sign up to set email alerts
|

Régiosélectivité et stéréosélectivité de l'hydroxylation homolytique des hydrocarbures par le peracide benzoïque

Abstract: JACQUES FOSSEY, DANIEL LEFORT, MASSOUD MASSOUDI, JEAN-YVES NEDELEC et JEANINE SORBA. Can. J. Chem. 63, 678 (1985).Des hydrocarbures cyclohexane, Me-cyclohexane et adamantane sont hydroxylts par le peracide benzoi'que selon un processus radicalaire. La rtgiostlectivitt en faveur des alcools tertiaires atteint 60 B 90%. Pour les dkcalines cis et trans, la sttrtostlectivitt des dCcalols-9 peut atteindre 97%. Une trks bonne stCrCostlectivitC d'hydroxylation par un peracide ne signifie pas obligatoirement que la r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 10 publications
(7 reference statements)
1
13
0
Order By: Relevance
“…There are a number of chemical systems that will carry out saturated hydrocarbon hydroxylation in the absence of a metal. For example nitrosubstituted perbenzoic acids (Schneider & Müller, 1985), perbenzoic acid (Fossey et al, 1985), ozone and ground state (triplet) oxygen (Zadok & Mazur, 1982), hydrogen peroxide/ trifluoroacetic acid or trifluoroperacetic acid (Deno et al, 1977), dimethyldioxirane and derivatives (Murray et al, 1986;Mello et al, 1989), perfluorodialkyloxaziridines (Des-Marteau et al, 1993), and iert-butylhydroperoxide (Chenier et al, 1978) have all been used to perform this type of oxidation. Perbenzoic acid, triplet oxygen, and ierf-butyl hydroperoxide all utilize the same mechanism, hydrogen radical abstraction at the site of reaction and then recombination of the carbon centered radical and a hydroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of chemical systems that will carry out saturated hydrocarbon hydroxylation in the absence of a metal. For example nitrosubstituted perbenzoic acids (Schneider & Müller, 1985), perbenzoic acid (Fossey et al, 1985), ozone and ground state (triplet) oxygen (Zadok & Mazur, 1982), hydrogen peroxide/ trifluoroacetic acid or trifluoroperacetic acid (Deno et al, 1977), dimethyldioxirane and derivatives (Murray et al, 1986;Mello et al, 1989), perfluorodialkyloxaziridines (Des-Marteau et al, 1993), and iert-butylhydroperoxide (Chenier et al, 1978) have all been used to perform this type of oxidation. Perbenzoic acid, triplet oxygen, and ierf-butyl hydroperoxide all utilize the same mechanism, hydrogen radical abstraction at the site of reaction and then recombination of the carbon centered radical and a hydroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…21 We have now converted the p-ieri-butylcalix[4]arene 2 into tetracarbonate 3 and report here the X-ray crystal and molecular structure of the 1:1 clathrate formed by 3 and acetonitrile. This is the first crystal structure reported of a clathrate of a nonaromatic guest and a p-ferf-butylcalix [4]arene. It is also the first functionalized calixarene to bind a neutral guest in the true clathrate sense.…”
mentioning
confidence: 85%
“…Furthermore, inclusion of aromatic guests was observed only when the para position of the calixarene carried a iert-butyl group, an arrangement believed to provide favorable CH3-7r interaction between the methyl groups and the system of the guest molecule. The iert-butyl groups are unable to bend inwards, thus blocking the entrance to the cavity as appears to be the case with p-(l,l,3,3-tetramethylbutyl)calix [4]arene.18…”
mentioning
confidence: 99%
“…Molecular oxygen, hydrogen peroxide, tert -butyl hydroperoxides, and peroxyacids were used as oxidants in these oxygenations. Certain complexes of transition metals have been previously reported to oxidize organic compounds including alkanes with meta -chloroperoxybenzoicacid (MCPBA [25]) [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44] (see, for example, complexes of cobalt [21,24,38], manganese [26,27,34,36,44], iron [28], nickel [30,31,32,33,35,37,39,42,43] and vanadium [40]). Earlier, Nam [15,16] reported that alkane oxidation with MCPBA catalyzed by some cobalt compounds proceeds stereoselectively.…”
Section: Introductionmentioning
confidence: 99%